The IL-4/STAT6 signaling axis establishes a conserved microRNA signature in human and mouse macrophages regulating cell survival via miR-342-3p. Issue 1 (December 2016) - Czimmerer, Zsolt; Varga, Tamas; Kiss, Mate; Vázquez, Cesaré; Doan-Xuan, Quang; Rückerl, Dominik; Tattikota, Sudhir; Yan, Xin; Nagy, Zsuzsanna; Daniel, Bence; Poliska, Szilard; Horvath, Attila; et al.
Abstract Background IL-4-driven alternative macrophage activation and proliferation are characteristic features of both antihelminthic immune responses and wound healing in contrast to classical macrophage activation, which primarily occurs during inflammatory responses. The signaling pathways defining the genome-wide microRNA expression profile as well as the cellular functions controlled by microRNAs during alternative macrophage activation are largely unknown. Hence, in the current work we examined the regulation and function of IL-4-regulated microRNAs in human and mouse alternative macrophage activation. Methods We utilized microarray-based microRNA profiling to detect the dynamic expression changes during human monocyte–macrophage differentiation and IL-4-mediated alternative macrophage activation. The expression changes and upstream regulatory pathways of selected microRNAs were further investigated in human and mouse in vitro and in vivo models of alternative macrophage activation by integrating small RNA-seq, ChIP-seq, ChIP-quantitative PCR, and gene expression data. MicroRNA-controlled gene networks and corresponding functions were identified using a combination of transcriptomic, bioinformatic, and functional approaches. Results The IL-4-controlled microRNA expression pattern was identified in models of human and mouse alternative macrophage activation. IL-4-dependent induction of miR-342-3p and repression of miR-99b along with miR-125a-5p occurred in both human and murine macrophages in vitro. In addition, a similar expression pattern was observed in peritoneal macrophages ofBrugia malayi nematode-implanted mice in vivo. By using IL4Rα- and STAT6-deficient macrophages, we were able to show that IL-4-dependent regulation of miR-342-3p, miR-99b, and miR-125a-5p is mediated by the IL-4Rα–STAT6 signaling pathway. The combination of gene expression studies and chromatin immunoprecipitation experiments demonstrated that both miR-342-3p and its host gene, EVL, are coregulated directly by STAT6. Finally, we found that miR-342-3p is capable of controlling macrophage survival through targeting an anti-apoptotic gene network including Bcl2l1. Conclusions Our findings identify a conserved IL-4/STAT6-regulated microRNA signature in alternatively activated human and mouse macrophages. Moreover, our study indicates that miR-342-3p likely plays a pro-apoptotic role in such cells, thereby providing a negative feedback arm to IL-4-dependent macrophage proliferation.